Customizing Proteins: Reassigning Functionality of Proteins via Incorporation of Unnatural Amino Acids - Jayawant, Maharsh; Kayalvizhi, Nagarajan; Krishnan, Muthukalingan; Wilson, Santhoshkumar Aruni; Rameshkumar, Neelamegam (Protein and Peptide Letters, 2025)
The natural horizon of the genetic code has expanded to incorporate amino acids, such as selenocysteine and pyrrolysine. Researchers have incorporated unnatural amino acids (UAAs) into target proteins, demonstrating increased protein functionality depending on their choice and target. The primary challenge in protein engineering is identifying novel antimicrobial short peptides effective against ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter spp.), which are categorized as multidrug-resistant (MDR). UAAs can be preferentially incorporated into short peptides to display therapeutic activity, potentially leading to next-generation targeted therapeutics. In purview of this, we have curated and summarized the applicability of genetic incorporations of UAAs in antimicrobial short peptides with a special emphasis on the importance of green synthesis. The approach affirmed a reduction in the toxicity of peptide drugs, making it biocompatible. This is an efficient protocol to develop novel antimicrobial short peptides catering to precision medications, particularly against MDR pathogens, as a sustainable pharmaceutical approach.
Keywords: UAAs